Gambaran Kekuatan Otot Ekstremitas Atas dan Bawah pada Lanjut Usia di Panti Werdha Griya Asih Lawang Kabupaten Malang - Yolla Yohanna Febriyantie; Sahda Eka Ardiyanti; Yuni Asri; Amin Zakaria; Elvianto Wihatno (Inovasi Kesehatan Global, 2024)
Increasing age will reduce the physiological functions of the body including muscle mass. The ability to synthesize muscle protein decreases due to a reduction in the number of muscle fibers and a decrease in muscle fiber size. This results in the loss of neurons, reducing muscle strength capacity. Decreased muscle strength limits the daily activities of the elderly, such as difficulty walking, climbing stairs, and lifting weights. The purpose of this study was to determine the description of upper and lower extremity muscle strength of the elderly in Griya Asih Lawang nursing home, Malang Regency. This descriptive study used 30 populations with a sampling technique that is total sampling. The variable in this study is the strength of the upper and lower extremities of the elderly measured using Manual Muscule Testing. Univariate data analysis, then the data is presented in a frequency distribution table. This research was conducted in June 2023 at Griya Asih Lawang nursing home, Malang Regency. The results showed that more than half of the respondents as many as 18 people (60%) had moderate muscle strength in the upper extremities and less than half as many as 13 people (43.5%) had low muscle strength in the lower extremities, and less than half as many as 13 people (43.5%) also had moderate muscle strength in the lower extremities. Elderly gymnastics efforts to prevent early muscle decline. Providing the right walking aids as needed in daily activities can minimize the risk of falls.